The Inequality We Want: How Much Is Too Much? - Alice Krozer (Luxembourg Income Study (LIS), 2017)
A key aspect defining the contemporary income distribution is the (increasing) share the top holds compared to the rest. This paper shows that income concentration increases towards the very top of the distribution, while the shares the middle- and upper-middle-income groups hold remain stable across countries and over time. Traditional indicators less sensitive to changes at the extremes of the distribution might obscure inequality's actual dimension, and thereby help perpetuate it. To avoid this, the present paper discusses a complementary indicator for the measurement of inequality: the ratio of the income share of the top 5 per cent over that of the bottom 40 per cent. The indicator is conceptually related to the recently suggested 'Palma ratio' dividing the income share of the top 10 per cent income earners by that of the bottom 40 per cent's.
Keywords: D31; D63; I3; 330; Inequality; Income Distribution; Poverty; Palma; Gini Coefficient